2019
DOI: 10.2478/acve-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selenium on the Morphology of Immune System Organs in Healthy Broilers

Abstract: This study aimed to establish the effect of dietary supplementation in broiler chickens of organic and inorganic selenium on the weight and structure of the thymus, bursa of Fabricius and spleen. Three dietary regimes were studied in Flex and F15 Hubbard chickens: (i) control, (ii) diets containing 0.5 mg organic selenium/kg by selenized yeast, (iii) diets supplemented with 0.5 mg ionic selenium/kg (sodium selenite). The results showed that the feed additives did not affect the relative weight of the immune sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…However, the enlarged heart of DHQ fed birds is difficult to explain without further pathological and anatomical investigation. Korzeniowska et al (2019) did not find differences between the relative weight of the spleen in birds fed selenium as an antioxidant. Khan et al (2010) reported an increase in the relative weight of liver of hens with aflatoxicosis.…”
Section: Growth Performance and Relative Organ Weightsmentioning
confidence: 58%
“…However, the enlarged heart of DHQ fed birds is difficult to explain without further pathological and anatomical investigation. Korzeniowska et al (2019) did not find differences between the relative weight of the spleen in birds fed selenium as an antioxidant. Khan et al (2010) reported an increase in the relative weight of liver of hens with aflatoxicosis.…”
Section: Growth Performance and Relative Organ Weightsmentioning
confidence: 58%
“…Moreover, Se is not only essential for humans but also animals and poultry [16,17]. It was found that the level of 0.25 mg kg −1 diet of organic Se was adequate to enrich eggs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, GPx enables the reparation of complex molecules (e.g. cell membrane lipids) [21]. The specifi c structure of sperm cell plasma membrane, which is rich in unsaturated fatty acids, is targeted by free radicals, which points to the importance of GPx in the protection from damage caused by peroxides.…”
Section: Introductionmentioning
confidence: 99%